Summer of soul (... or when the revolution could not be televised) [videorecording (DVD)] - Wonder, Stevie; Simone, Nina, 1933-2003; Jackson, Mahalia, 1911-1972; King, B. B.; Ruffin, David; Santamaria, Mongo; Barretto, Ray; Mann, Herbie, 1930-2003; Roach, Max, 1924-2007 (20th Century Studios, 2022)
In his acclaimed debut as a filmmaker, Ahmir "Questlove" Thompson presents a powerful and transporting documentary, part music film, part historical record, created around an epic event that celebrated Black history, culture, and fashion. Over the course of six weeks in the summer of 1969, just one hundred miles south of Woodstock, The Harlem Cultural Festival was filmed in Mount Morris Park (now Marcus Garvey Park). The footage was largely forgotten, until now. This documentary shines a light on the importance of history to our spiritual well-being and stands as a testament to the healing power of music during times of unrest, both past, and present. The feature includes concert performances by Stevie Wonder, Nina Simone, Sly & the Family Stone, Gladys Knight and the Pips, Mahalia Jackson, B.B. King, The 5th Dimension, and more.